ANALISIS PENERAPAN METODE TALAQQI TERHADAP PENINGKATAN HAFALAN AL-QUR’AN DI SMAIT AL-USWAH BANGIL - Khylwa Butolo; Istikomah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The Qur'an, as the word of God, must be believed in and memorized correctly. SMAIT Al-Uswah Bangil, an Integrated Islamic high school, implements a tahfidz program using the talaqqi method to improve students’ Qur'an memorization skills. Talaqqi is a learning process that involves direct face-to-face interaction between teachers and students to recite and submit Qur'an memorization. This study employs a descriptive qualitative approach with the principal, tahfidz teachers, and students as research subjects. The results indicate that the talaqqi method effectively enhances Qur'an memorization, especially for students who are still learning tajwid rules, although it is less effective for students who already have good Qur'an reading skills. The tahfidz program at SMAIT Al-Uswah is also supported by Arabic language programs and dormitory systems to optimize memorization activities. This study presents a comprehensive view of the successes and challenges in applying the talaqqi method in tahfidz learning at an integrated Islamic school.